Progressive skin fibrosis is associated with a decline in lung function and worse survival in patients with diffuse cutaneous systemic sclerosis in the European Scleroderma Trials and Research (EUSTAR) cohort - (:unkn) unknown (BMJ PUBLISHING GROUP, 2019)
Objectives To determine whether progressive skin fibrosis is associated with visceral organ progression and mortality during follow-up in patients with diffuse cutaneous systemic sclerosis (dcSSc). Methods We evaluated patients from the European Scleroderma Trials and Research database with dcSSc, baseline modified Rodnan skin score (mRSS) >= 7, valid mRSS at 12 +/- 3 months after baseline and >= 1 annual follow-up visit. Progressive skin fibrosis was defined as an increase in mRSS >5 and >= 25% from baseline to 12 +/- 3 months. Outcomes were pulmonary, cardiovascular and renal progression, and all-cause death. Associations between skin progression and outcomes were evaluated by Kaplan-Meier survival analysis and multivariable Cox regression. Results Of 1021 included patients, 78 (7.6%) had progressive skin fibrosis (skin progressors). Median follow-up was 3.4 years. Survival analyses indicated that skin progressors had a significantly higher probability of FVC decline >= 10% (53.6% vs 34.4%; p<0.001) and all-cause death (15.4% vs 7.3%; p=0.003) than non-progressors. These significant associations were also found in subgroup analyses of patients with either low baseline mRSS (<= 22/51) or short disease duration (<= 15 months). In multivariable analyses, skin progression within 1 year was independently associated with FVC decline >= 10% (HR 1.79, 95% CI 1.20 to 2.65) and all-cause death (HR 2.58, 95% CI 1.31 to 5.09). Conclusions Progressive skin fibrosis within 1 year is associated with decline in lung function and worse survival in dcSSc during follow-up. These results confirm mRSS as a surrogate marker in dcSSc, which will be helpful for cohort enrichment in future trials and risk stratification in clinical practice.
Keywords: THICKNESS SCORE; PROGNOSTIC-FACTORS; PREDICTION; INVOLVEMENT; MORTALITY; DEATH; VARIABILITY; IMPROVEMENT; VALIDATION